An investigation of the relationship between fundamental movement skill proficiency and health in Singaporean children at the primary school entry level - Khong, Serena Wei Jia. (2013)
Fundamental movement skills (FMS) proficiency is most successfully acquired during the elementary years. Lack of appropriate motor skill instructions and practice may cause developmental delays in children’s gross motor abilities. FMS proficiency has been found to be positively associated with health and physical fitness, and proficient movers are likely to become physically active adolescents. However, the relationship between FMS proficiency and health is yet to be clearly elucidated in Singaporean children at the primary school entry level. Therefore, this study aimed to determine the FMS proficiency levels and investigate the relationship of FMS proficiency and health status in this population. Participants were Singaporean children at the primary school entry level from four primary schools (n=120). The Test of Gross Motor Development 2 (TGMD-2) was used to assess participants’ locomotor skills (run, gallop, hop, leap, jump, and slide) and object control skills (strike, dribble, catch, kick, throw, and roll). The 20m shuttle run test was administered to determine their cardiovascular fitness, while height, weight, body mass index (BMI), waist and hip circumferences, waist-hip ratio and waist-height ratio were measured to evaluate their metabolic health status. Results showed that the participants’ FMS proficiency levels were generally below that of the normative sample (mean GMQ percentile=8.7±7.7 (boys) and 10.2±9.5 (girls)), and FMS proficiency has stronger relationships with cardiovascular fitness than metabolic health in this age group. The results highlight the importance of providing Singaporean children with greater opportunities to practice and develop their FMS through structured programs even before they enter primary school.